Nigeria’s Traditional Virtue Ethics and Business: An Ibibio Virtue Ethics Approach to Business Ethics - Okpo, Odumayak (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
The concern of this paper is the application of a Nigerian traditional virtue-based ethics to business. The Ibibio traditional virtue ethics was employed to achieve the purpose of this paper. The philosophical methods employed in this paper include analytical, speculative, and hermeneutic methods. The Nigerian business persons’ attitudes towards ethics in business can hardly bring about business sustainability because many of them lack strong moral character needed. Morality sets the limits of cooperation and creates conditions necessary if cooperation is to be achieved. Business is a good example of an area of human activity that rests on cooperation. This work examines the application of traditional Ibibio virtue ethics to some ethical issues in business both in the past and the contemporary period. It argues that business persons need to reinvent the traditional Ibibio virtue ethics, change their attitude and making honesty, integrity, justice, service to others, moral courage, and respect for others be their guiding principles in their business transactions.